P–440 Seven years' experience using oocyte vitrification/warming from in vitro maturation or controlled ovarian hyperstimulation cycles to preserve fertility for oncologic indications. (6th August 2021) - Boumerdassi, Y; Bennan. Smires, B; Sarandi, S; Sadoun, M; Laup, L; Labrosse, J; Herbemont, C; Vinolas, C; Cedrin-Durnerin, I; Peigné, M; Sermondade, N; Grynberg, M; et al.
Abstract: Study question: Do oocytes vitrified following in vitro maturation (IVM) or controlled ovarian hyperstimulation (COH) for oncologic fertility preservation (FP), lead to similar biological/clinical outcomes after thawing? Summary answer: IVM is a valid option when chemotherapy is urgent or COH is contraindicated. We report the second live-birth worldwide after IVM in a cancer patient. What is known already: FP aims at maintaining in cancer survivors, the possibility of childbearing using their own gametes. Currently, oocyte vitrification after COH remains the gold standard but IVM has recently emerged as an option for young women seeking FP, when COH is contraindicated or when cancer therapy is urgent. However, the actual competence of oocyte vitrified after IVM in cancer patients is not established. To date, only one live birth has been reported following frozen/warmed oocytes from an IVM cycle and no data is available comparing biological/clinical outcomes of warmed oocytes resulting either from IVM or COH cycles in cancer survivors. Study design, size, duration: This retrospective cohort study from a single IVF unit aimed to analyze outcomes of all oocyte warming cycles in 38 cancer survivors having undergone oocyte vitrification for FP after COH or IVM. All of them had oocyte retrieval before administration of gonadotoxic treatment and returned after being cured for assisted reproduction treatments with their oncologist agreement, between January 2014 and December 2020. Participants/materials, setting, methods: Thirty-eight oocytes warming cycles followed by ICSI respectively from 18 COH and 22 IVM cycles were analyzed. Survival, degeneration following ICSI, fertilization, top-quality and good-quality embryos, defined at day–2 respectively as 4 and 3–5 adequate-sized blastomeres, without multinucleation and containing <20% of cytoplasmic fragments, implantation, biochemical (hCG>100 UI/mL), clinical (intrauterine sac with fetal heart beat) and live birth rates were compared between IVM and COH cycles using appropriate statistical tests. Significance was set at 5%. Main results and the role of chance: The indications for FP were breast cancer (n = 32), hematologic malignancies (n = 3), BRCA1 mutation (n = 2), borderline ovarian tumor (n = 1). The mean age and antral follicle count (AFC) at the time of FP was similar in both groups. The number of cryopreserved oocytes was significantly lower in the IVM group (5.7 ± 9.1) when compared with the COH group (11.4 ± 3.3; p = 0.009). Oocyte survival rates were similar in IVM (70 ± 24%) and COH groups (73 ± 28%). Although not significant, we reported a trend to better results in the COH group when compared with those of IVM group in terms of degeneration rate following ICSI (6 ± 10% vs. 14 ± 20%; p = 0.16), fertilization (72 ± 35% vs. 54 ± 27%; p = 0.08), day 2 top-quality (38 ± 32% vs. 21 ± 31%; p = 0.15) and good-quality embryo (46 ± 30% vs. 25 ± 30%; p = 0.06), implantation (18 ± 35% vs. 14 ± 36%; p = 0.79), biochemical (28 (5/18) vs. 14% (3/22); p = 0.26), clinical (22% (4/18) vs. 9% (2/22); p = 0.24), live birth rates (22% (4/18) vs. 5% (1/22); p = 0.06). Limitations, reasons for caution: Caution is needed when interpreting these retrospective data obtained from a limited number of frozen-thawed cycles. Statistical power to compare IVF outcomes after COH and IVM is limited by the few women who return for oocyte reutilization. Wider implications of the findings: The present investigation is the largest evaluating the IVM-oocyte frozen-thawed cycles in a oncologic population. It suggests that a higher oocyte yield may be necessary in IVM, since fertilization/embryo-quality rates seem lower. Success rates and limiting factors of oocyte vitrification in this context is needed for providing proper oncofertility counseling. Trial registration number: Not applicable